Detection and Removal of Polycyclic Aromatic Hydrocarbon from Selected Areas in Tigris River in Baghdad City (Journal of Engineering, 2013)
Aromatic hydrocarbons present in Iraqi national surface water were believed to be raised principally from combustion of various petroleum products, industrial processes and transport output and their precipitation on surface water.Polycyclic aromatic hydrocarbons (PAHs) were included in the priority pollutant list due to their toxic and carcinogenic nature. The concern about water contamination and the consequent human exposure have encouraged the development of new methods forPAHs detection and removal.PAHs, the real contaminants of petroleum matter, were detected in selected sites along Tigris River within Baghdad City in summer and winter time, using Shimadzu high performance liquid chromatography (HPLC) system.Analysis of samples from selected sites proved that the most abundant component of aromatic hydrocarbons were phenanthrene naphthalene, and acenaphthylene, followed by fluorene, acenaphthene, fluoranthene, benzo (a) pyrene, anthracene. and pyrene werepresent in low concentrations ranging in a descending order. Chrysene and benzo (a) anthracene were found in very low concentration.A laboratory unit was designed to optimize the factors which may influence the feasibility of degradation processes of naphthalene and phenanthrene in aqueous matrices by oxidation with Fenton reagent. The study proved that 83% and 79% removal of naphthalene and phenanthrene were achieved applying optimum conditions of pH=3, temperature=40 ° C, H2O2=50 ppm and Fe2+ catalyst = 6 ppm